Analisis Tingkat Literasi Akuntansi Studi Kasus pada Mahasiswa Akuntansi di Bengkalis - Novia Delisa Damanik; Nurhazana Nurhazana (LPPM Institut Pendidikan Nusantara Global, 2025)
Accounting students continue to experience difficulties in accurately recording financial transactions, particularly in preparing journal entries, posting to the general ledger, and compiling financial statements. These challenges contribute to low levels of accounting literacy, which reflects students’ ability to understand, analyze, and apply fundamental accounting concepts in real practice. In response to this issue, the present study aims to analyze the simultaneous influence of three key factors: transaction recording practices, understanding of recording objectives, and recording routines on the accounting literacy of Accounting students in Bengkalis. This study adopts a quantitative research method with an associative approach to examine the relationships among variables. The sample consisted of 201 Accounting students selected through purposive sampling based on specific criteria relevant to the research objectives. Data were gathered using a structured questionnaire employing a Likert scale to measure students’ perceptions and behaviors related to accounting practices. The collected data were then processed and analyzed using multiple linear regression with SPSS version 25 to determine both partial and simultaneous effects of the independent variables on accounting literacy. The results reveal that transaction recording practices, understanding of the objectives of financial recording, and consistent recording routines each have a positive and significant effect on students’ accounting literacy. These findings indicate that when students implement recording procedures correctly, possess a clear understanding of the purpose behind financial documentation, and engage in regular practice, their accounting literacy improves substantially. In other words, strengthening practical skills and conceptual understanding contributes meaningfully to enhancing students’ overall accounting competence.